2017
DOI: 10.7600/jpfsm.6.65
|View full text |Cite
|
Sign up to set email alerts
|

CDK inhibitors for muscle stem cell differentiation and self-renewal

Abstract: Regeneration of muscle is undertaken by muscle stem cell populations named satellite cells which are normally quiescent or at the G0 phase of the cell cycle. However, upon signals from damaged muscle, satellite cells lose their quiescence, and enter the G1 cell cycle phase to expand the population of satellite cell progenies termed myogenic precursor cells (MPCs). Eventually, MPCs stop their cell cycle and undergo terminal differentiation to form skeletal muscle fibers. Some MPCs retract to quiescent satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…This locus is epigenetically silenced in fetal, embryo and adult stem cells; however, it can be reprogrammed in differentiated cells to become hyper-responsive to mitogenic signals. 6 Most senescent cells express p16 7 that blocks cell cycle by inhibiting CDK4/CDK6 8 hence making p16 a commonly recognized senescence marker. 9 Pathologies aside, senescence also occurs in embryogenesis presumed to play roles in maintaining embryonic structures or regulating restructuring of organs.…”
Section: Introductionmentioning
confidence: 99%
“…This locus is epigenetically silenced in fetal, embryo and adult stem cells; however, it can be reprogrammed in differentiated cells to become hyper-responsive to mitogenic signals. 6 Most senescent cells express p16 7 that blocks cell cycle by inhibiting CDK4/CDK6 8 hence making p16 a commonly recognized senescence marker. 9 Pathologies aside, senescence also occurs in embryogenesis presumed to play roles in maintaining embryonic structures or regulating restructuring of organs.…”
Section: Introductionmentioning
confidence: 99%
“…Other noticeable downregulated genes comprised those encoding the Ki-67 protein and the topoisomerase IIa, well-known cell cycle-related markers [ 38 ], the ID1 myogenesis inhibitor [ 39 ], and the c-Myb, which inhibit myogenic differentiation through the repression of MyoD [ 40 ]. In summary, the functions of these significantly downregulated genes are related to the inhibition of the cell cycle, which is required for muscle differentiation in physiological conditions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fourth network identified by IPA had nodes related to two of the top upstream regulators, CDKN1A (p21) and Rb. CDKN1A induces cell cycle arrest by inhibiting cyclin-depen- dent kinase activity, a key regulator of cell cycle initiation and progression (30). Machida and Booth (24) demonstrated that SCs from aged animals, which have reduced proliferation, have increased nuclear p21 WAF1/CIP1 and p27 Kip1 .…”
Section: Discussionmentioning
confidence: 99%
“…Machida and Booth (24) demonstrated that SCs from aged animals, which have reduced proliferation, have increased nuclear p21 WAF1/CIP1 and p27 Kip1 . Rb also induces cell cycle arrest by inhibiting transcription factors of the E2F family; E2F transcription factors push cells into S phase and promote progression through the cell cycle (30). E2F was predicted to be an "active" upstream regulator in the FAST and CDKN1A and Rb were predicted to be "inhibited."…”
Section: Discussionmentioning
confidence: 99%